The Federal Democratic Republic of Ethiopia : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
Ethiopia pursues a public sector-led growth strategy that focuses on promoting growth through high public investment supported partly by low nominal interest rates. While the strategy has contributed to robust economic growth in the past, recent developments indicate a buildup of vulnerabilities which need to be addressed in order to sustain this growth performance. While inflation remains high (21 percent at end-2011/12), real GDP growth, which is estimated at around 7 percent in 2011/12 and is projected to decline to 6.5 percent in subsequent years under the continuation of current policies, is still robust.